Nitric oxide and mitochondria in metabolic syndrome - Litvinova, Larisa; Atochin, Dmitriy N.; Fattakhov, Nikolai; Vasilenko, Mariia; Zatolokin, Pavel; Kirienkova, Elena (Frontiers in Physiology, 2015)
Metabolic syndrome (MS) is a cluster of metabolic disorders that collectively increase the risk of cardiovascular disease. Nitric oxide (NO) plays a crucial role in the pathogeneses of MS components and is involved in different mitochondrial signaling pathways that control respiration and apoptosis. The present review summarizes the recent information regarding the interrelations of mitochondria and NO in MS. Changes in the activities of different NO synthase isoforms lead to the formation of metabolic disorders and therefore are highlighted here. Reduced endothelial NOS activity and NO bioavailability, as the main factors underlying the endothelial dysfunction that occurs in MS, are discussed in this review in relation to mitochondrial dysfunction. We also focus on potential therapeutic strategies involving NO signaling pathways that can be used to treat patients with metabolic disorders associated with mitochondrial dysfunction. The article may help researchers develop new approaches for the diagnosis, prevention and treatment of MS.